Learning Strategy in Nursing Education toward The Development of The Twenty-First Century Learning Skills - ส่งวัฒนายุทธ, ปาณิสรา -; ศรีเกษตริน, อติญาณ์; ปาณะวัฒนพิสุทธิ์, สุภาเพ็ญ (Journal of The Royal Thai Army Nurses, 2019)
Learning strategy in nursing education toward the development of the twenty-First century skills has objective is to propose guidelines for the development and adjustment of effective teaching and learning in nursing. This article presents the ACTIVE Model as follows: A (Atmosphere of Learning) C (Culture differences) T (Transformative learning) I (Information andtechnology) E (Empowerment) that lead to develop of competent nursing graduates according to the needs of the health system in the 21st century world.